Biomimetic rearrangements of simplified labdane diterpenoids - George, J; McArdle, M; Baldwin, J; Adlington, R (2010)
Simplified ethyl-substituted labdane diterpenoids 14 and 19 have been synthesised from (+)-sclareolide (18). Biomimetic rearrangements of these compounds, involving stereospecific 1,2-alkyl and hydride shifts, have been carried out by treatment with a variety of Lewis and protic acids. Halimane compounds, such as 34 and simple dehydration products such as 3, 32 and 33 have been formed either selectively or as mixtures depending on the reaction conditions. However, further rearrangement to clerodane products such as 1 and 2 was not observed, indicating a high degree of enzymatic control for the in vivo formation of these natural products. © 2010 Elsevier Ltd.